2017
DOI: 10.1097/md.0000000000006076
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative centration during small incision lenticule extraction (SMILE)

Abstract: To evaluate intraoperative decentration from pupil center and kappa intercept during small incision lenticule extraction (SMILE) and its impact on visual outcomes.This was a retrospective noncomparative case series. A total of 164 eyes that underwent SMILE at the Singapore National Eye Center were included. Screen captures of intraoperative videos were analyzed. Preoperative and 3 month postoperative vision and refractive data were analyzed against decentration.The mean preoperative spherical equivalent (SE) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
2
15
1
1
Order By: Relevance
“…Hence, the patient should be informed to fixate on the green light during the whole process of docking. The mean decentrations for CSCLR and pupillary center were 0.20 mm in the current study, and this was within the range of values of 0.17 to 0.36 mm published in the earlier reports [68, 19, 20]. Decentration that do not exceed 0.3 mm is rarely considered to be visually significant [21].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Hence, the patient should be informed to fixate on the green light during the whole process of docking. The mean decentrations for CSCLR and pupillary center were 0.20 mm in the current study, and this was within the range of values of 0.17 to 0.36 mm published in the earlier reports [68, 19, 20]. Decentration that do not exceed 0.3 mm is rarely considered to be visually significant [21].…”
Section: Discussionsupporting
confidence: 87%
“…Currently, there are fewer studies that reported the evaluation of SMILE decentration and its effect on visual outcomes. Wong et al found no statistical difference in postoperative visual acuity among the different pupillary decentration applied eyes, and then the centration was attempted on the pupil center in this study [8]. Li also reported good visual outcomes despite mild decentration [5].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Unlike LASIK and FS-LASIK, SMILE does not incorporate intracapsular flushing of the corneal stroma after the removal of microlenses into the standard operation procedure. Most surgeons believe that irrigation can limit corneal epithelium growth into the cornea along the edge of the corneal incision, remove inflammatory factors and reduce infectious microorganisms during surgical procedures; thus, it can reduce the risk of infection after surgery [9][10][11][12]. We suspect that the pocket interface after irrigation is smoother and that adherence to the upper and lower contact surfaces is better, thus contributing to early visual recovery.…”
Section: Introductionmentioning
confidence: 99%